BS IEC 62631-2-2. Dielectric and resistive properties of solid insulating materials. Part 2-2. Relative permittivity and dielectric dissipation factor. High frequencies (1 MHz to 300 MHz). AC Methods (21st November 2020) - British Standards Institution,
No abstract available